Efektivitas Jalur Hijau Jalan dalam Mengurangi Polutan Gas CO - Anisah Nur Izzah; Nizar Nasrullah; Bambang Sulistyantara (Jurnal Ilmu Pertanian Indonesia, 2019)
Air pollution is a serious problem that increase in almost all countries, including in developed countries. Increasing in air pollution is generally caused by human activity such as transportation. One of dangerous pollutant substances generated by motor vehicles is CO (carbon monoxide) gas. One effort in controlling air pollution is the utilization of green open space in the roadside area. The purpose of this study is to determine the distribution of CO in road side vegetation area and open area. The research was conducted in roadside green belt of Cikampek Highway. Air sampling was conducted to measure the concentration of CO in the distances of 0, 10, and 30 m from green belt area. Concentration of CO was analyzed using a spectrophotometry method. The result showed that vegetation and distance factors significantly affected the distribution of CO gas concentrations.The existance green belt area reduced the distribution of CO pollutant in the vicinity of Cikampek highway. As a result, the plot of vegetation area can effectively reduce the concentration of CO gas by 8.5% compare to open plot area. In this study, the plot of vegetation area at10 and 30 m distances decreased CO concentrations about 14.5 and 23.55%, respectively. In the open plot area, the 10 and 30 m distances from the open plot area decreased CO concentrations by 7.17 and 15.05%, respectively.